2017
DOI: 10.1111/add.13869
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes, quit attempts and smoking cessation: a 6-month follow-up

Abstract: Among people who smoke, those also using an e-cigarette regularly are more likely to try to quit smoking and reduce their cigarette consumption during the next 6 months. It remains unclear whether regular e-cigarette users are also more likely to stop smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 18 publications
5
48
1
Order By: Relevance
“…It is possible that there is a link here: for example, the new legislation may have led to fewer tobacco smokers using e-cigarettes, and therefore fewer people stopped smoking. Other studies have already demonstrated a similar connection (24,25).…”
Section: Discussionsupporting
confidence: 63%
“…It is possible that there is a link here: for example, the new legislation may have led to fewer tobacco smokers using e-cigarettes, and therefore fewer people stopped smoking. Other studies have already demonstrated a similar connection (24,25).…”
Section: Discussionsupporting
confidence: 63%
“…Adult vaping prevalence in selected western countries. Australia , Germany , Sweden , Finland , European Union , Canada , United States , France , New Zealand , Greece and Great Britain .…”
Section: Is There Enough Vaping To Influence Population Smoking Rates?mentioning
confidence: 99%
“…Although millions of smokers are simultaneously using ECIGs [9, 10], for the purpose of quitting smoking, they usually do so without receiving any behavioral assistance. In addition, although more likely to make a quit attempt than smokers alone, they are not significantly more likely to actually quit [11]. Thus, an opportunity exists to facilitate smoking cessation among the large population of “dual users” who have demonstrated initial action toward smoking cessation by initiating ECIGs and are primed to benefit from a minimal intervention to enhance their chances of tobacco abstinence.…”
Section: Introductionmentioning
confidence: 99%